Jawabanmu

2014-08-30T16:09:27+07:00
1. ( 4x + 2 ) ( 2x-3 ) = 8x² - 12x + 4x- 6
                             = 8x² - 8x - 6
2. ( x -2 )( x + 2 ) = x² +2x-2x-4
                         = x² -4
3. 2x ( 3x+2 ) = 6x²+4x
4. 6x²( x - 5 ) = 6x³-30x²
5. ( x-15)(x+2) = x²+2x-15x-30
                     = x²-13x-30
Jawaban paling cerdas!
2014-08-30T16:10:10+07:00
1. 4x(2x-3) +2(2x-3) =  8x kuadrat -12x +4x -6 =8x kuadrat -8x -6
2 x(x-2)+2(x-2) = x kuadrat -2x +2x -4 = x kuadrat -4
3. 2x (3x+2) = 6x kuadrat + 4x
4. 6x kuadrat (x-5) =
5. x(x+2)
1 5 1